Tutorial on high-performance liquid chromatography of isotopologues of organic compounds - P.N. Nesterenko; V.D. Kazakova (Journal of Chromatography Open)
Separation of isotopologues or chemical species having different number of neutrons in one or more atoms of specific compound represents an important but difficult task. Application of high-performance liquid chromatography (HPLC) provides some flexibility in various separation modes of isotopologues via different isotopic effects. This tutorial describes basic isotopic effects (hydrophobicity, polarizability, acid-base properties, size difference, etc.), which can influence HPLC performance in the separation of isotopologues. The article is focused on separation selectivity of deuterated organic compounds, for which different properties are considered. The use of advanced adsorption materials and techniques is discussed.